Rethinking Climate Change Governance and its Relationship to the World Trading System - Scott Barrett (Fondation pour les études et recherches sur le développement international (FERDI), 2011)
International climate negotiations have thus far eschewed efforts to incorporate trade restrictions, but they have also failed to achieve their objective of reducing global emissions. Because of this failure, some countries are now inclined to act unilaterally and minilaterally, in many cases by imposing trade restrictions against third parties. Such actions are likely to invite retaliation. They could even ignite an escalating trade war. The best way to avoid such conflicts is not to limit the use of trade restrictions but to make international climate negotiations effective. Ironically, success in addressing climate change multilaterally may require incorporating trade restrictions in a new kind of climate agreement.
Keywords: F18; F51; F53; Q54; 330